"About Perception". - Moving Space, Gent (Gent : Moving Space, 1991)
Hartung, Hans ; Coulon, Bernard ; De Smet, Yves ; Ilgen, Fre ; Massart, Cecile ; Paller, Gary ; Rompza, Sigurd ; Seynaeve, Johan ; Verroken, Andre
About Perception, Moving Space, Gent, 11.05.1991 - 09.06.1991
boek